Electrode slurry, preparation method and photovoltaic cell
By using nano silver powder and Sn-Zn-Ga-Nd alloy in the electrode paste, the problem of low welding and welding tension during the welding process of the heterojunction battery main gate silver paste is solved, and higher welding bonding and welding ability are achieved, and cost is reduced.
Patent Information
- Application Number
- CN202210977393.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-15
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2042-08-15
AI Technical Summary
The existing heterojunction battery main gate silver paste is prone to cause dummy welding during welding, resulting in low welding tension and inability to effectively combine with the welding belt.
An electrode slurry containing nano-silver powder and Sn-Zn-Ga-Nd alloy was used. The melting point of the nano-silver powder was about 100°C and the melting point of the Sn-Zn-Ga-Nd alloy was 176°C to 198°C. It melted in sequence when printing the main gate, promoting sintering to form a dense bonding phase, and improving the welding and adhesion of the film layer through capillary force.
The welding bonding force between the electrode paste and the welding tapes of the components when printing the main gate during battery manufacturing is improved, the welding tension and welding ability are enhanced, the use of silver conductive materials is reduced, and the cost is reduced.
Smart Images

Figure CN115223746B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of batteries, and in particular to an electrode slurry and a preparation method thereof, and a photovoltaic cell. Background Art
[0002] The middle of the heterojunction cell HJT cell is N-type crystalline silicon, and a double-sided cell structure is usually used. On one side of the crystalline silicon, an intrinsic amorphous silicon film and a P-type film are deposited in sequence, and on the other side, an intrinsic amorphous silicon film and an N-type film are deposited in sequence to form a PN junction. Since amorphous silicon has poor conductivity, a transparent conductive film (TCO) needs to be deposited on both sides of the cell to conduct electricity, and finally a double-sided electrode is formed by screen printing technology. Generally, step-by-step printing is used to meet the battery's requirements for electrical performance and welding tension. The main grid is mainly used to provide welding tension and collect current, and the secondary grid is mainly used to form a low contact resistance with the TCO layer to collect current.
[0003] The silver paste for the main grid of heterojunction batteries currently available on the market mainly relies on the cross-linking and curing of organic polymers to form contact between silver particles and between silver particles and TCO to provide adhesion. However, the coating of silver powder by organic polymer resin blocks the combination of the silver layer and the solder strip to a certain extent, which easily causes cold solder joints and low tensile strength. Therefore, it is very important to prepare an electrode paste that can enhance the ability to combine with the solder strip. Summary of the invention
[0004] The object of the present invention is to provide an electrode slurry and a preparation method thereof and a photovoltaic cell, which can improve the welding bonding strength between the electrode slurry and the welding strip of the component series welding when printing the main grid during the battery manufacturing process.
[0005] In a first aspect, the present invention provides an electrode slurry, comprising: a first conductive material and a second conductive material, wherein the first conductive material comprises at least nano silver powder, the second conductive material is a Sn-Zn-Ga-Nd alloy, and the melting point of the second conductive material is 176°C to 198°C.
[0006] Compared with the prior art, the electrode slurry provided by the present invention has the following advantages:
[0007] The electrode paste provided by the present invention includes a first conductive material and a second conductive material. Since the first conductive material at least includes nano silver powder, the melting point of the nano silver powder is about 100°C, and the second conductive material is Sn-Zn-Ga-Nd alloy, the melting point of the second conductive material is 176°C to 198°C, when sintering the printed main grid, the nano silver powder and the second conductive material can be melted in sequence. On the one hand, it can play a sintering-aiding role for the first conductive material, promote the sintering of the first conductive material to form a dense bonding phase, thereby increasing the conductive path and reducing the volume resistance of the main grid electrode. On the other hand, the Sn-Zn-Ga-Nd alloy can act on the surface of the transparent conductive film layer of the heterojunction battery through capillary force, and after cooling, an anchoring effect will be formed, which can further improve the welding force and adhesion of the film layer. At the same time, Ga in the Sn-Zn-Ga-Nd alloy is a surface active substance, which can reduce the surface tension of the melt and improve the wetting performance of the alloy in the system. It can increase the bonding force with the welding strip during welding and improve the weldability and peeling strength of the film layer. Nd is evenly dispersed in the alloy, which can effectively enhance the oxidation resistance of Sn-Zn. At the same time, when it is welded with the welding strip, it can generate intermetallic compounds with the solder on the welding strip and disperse on the grain boundary, thereby improving the mechanical properties of the crystal, playing a role of solid solution strengthening, improving the solder resistance and peeling strength of the film layer, and avoiding the aging failure problem and poor solderability problem caused by the simple organic resin as the bonding phase. In addition, since the second conductive material can replace part of the silver conductive material, the amount of silver conductive material used is reduced, reducing the cost.
[0008] As can be seen from the above, the electrode paste provided by the present invention can improve the welding bonding strength between the electrode paste and the welding strip of the component series welding when printing the main grid during the battery manufacturing process.
[0009] In a second aspect, the present invention further provides a method for preparing an electrode slurry, comprising:
[0010] The curing agent, the organic solvent and the organic auxiliary agent are uniformly mixed, and the polymerizable resin is added and mixed to obtain an organic carrier;
[0011] The first conductive material, the second conductive material and the organic carrier are mixed uniformly to obtain an electrode slurry.
[0012] Compared with the prior art, the beneficial effects of the method for preparing the electrode slurry provided by the present invention are the same as the beneficial effects of the electrode slurry of the first aspect, which will not be described in detail here.
[0013] In a third aspect, the present invention further provides a photovoltaic cell, wherein the photovoltaic cell comprises the electrode slurry provided by the present invention.
[0014] Compared with the prior art, the photovoltaic cell provided by the present invention includes the electrode slurry provided by the present invention, so the beneficial effects are the same as the beneficial effects of the electrode slurry in the first aspect, which will not be described in detail here. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The drawings described herein are used to provide a further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0016] Figure 1 A schematic diagram of the structure of a battery according to an embodiment of the present invention;
[0017] Figure 2 The figure is a flow chart of the preparation of the electrode slurry according to an embodiment of the present invention.
[0018] Reference numerals:
[0019] 100-battery, 101a-positive electrode, 101b-negative electrode, 102a-first amorphous silicon transparent conductive film layer, 102b-second amorphous silicon transparent conductive film layer, 103a-first intrinsic amorphous silicon film, 103b-second intrinsic amorphous silicon film, 104-P-type amorphous silicon film, 105-N-type amorphous silicon film. DETAILED DESCRIPTION
[0020] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0021] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined. The meaning of "several" is one or more, unless otherwise clearly and specifically defined.
[0022] Conventional crystalline silicon solar cells are made on a complete silicon wafer, using different doping processes to form an N-type semiconductor on one side and a P-type semiconductor on the other side, and a PN junction is formed in the area near the interface of the two semiconductors. The full name of heterojunction solar cells is intrinsic thin-film heterojunction cells (HJT, Heterojunction with Intrinsic Thin-layer), which is a special PN junction formed by amorphous silicon and crystalline silicon materials. It is a type of N-type cell that deposits an amorphous silicon thin film on crystalline silicon. Since the theoretical efficiency of heterojunction cells can reach 28%, which is much higher than conventional crystalline silicon solar cells, it has become one of the development directions of the next generation of solar cells.
[0023] The silver paste for the main grid of heterojunction batteries currently available on the market mainly relies on the cross-linking and curing of organic polymers to form contact between silver particles and between silver particles and TCO to provide adhesion. However, the coating of silver powder by organic polymer resin blocks the combination of silver layer and solder strip to a certain extent, which easily causes cold solder joints and low tensile strength.
[0024] In view of the above problems, an embodiment of the present invention provides a photovoltaic cell, which may include the electrode material of the embodiment of the present invention to improve the welding bonding strength between the electrode paste and the welding ribbon of the component string welding when printing the main grid during the battery manufacturing process. It should be understood that the photovoltaic cell can be a heterojunction cell, which may include an electrode material, a substrate, an amorphous silicon transparent conductive film layer, a P-type amorphous silicon film, an intrinsic amorphous silicon film, and an N-type amorphous silicon film. Figure 1 The schematic diagram of the structure of the battery of the embodiment of the present invention is shown as follows: Figure 1 As shown, the heterojunction battery 100 of the embodiment of the present invention comprises, from the front side of the battery from top to bottom, a positive electrode 101a, a first amorphous silicon transparent conductive film layer 102a, a P-type amorphous silicon film 104, a first intrinsic amorphous silicon film 103a, a substrate 106, a second intrinsic amorphous silicon film 103b, an N-type amorphous silicon film 105, a second amorphous silicon transparent conductive film layer 102b and a negative electrode 101b.
[0025] An electrode slurry provided in an embodiment of the present invention can be applied to the above photovoltaic cell, comprising: a first conductive material and a second conductive material, wherein the first conductive material at least comprises nano silver powder, and the second conductive material is a Sn-Zn-Ga-Nd alloy, and the melting point of the second conductive material is 176°C to 198°C.
[0026] The electrode paste provided by the present invention includes a first conductive material and a second conductive material. Since the first conductive material at least includes nano silver powder, the melting point of the nano silver powder is about 100°C, and the second conductive material is Sn-Zn-Ga-Nd alloy, the melting point of the second conductive material is 176°C to 198°C, when sintering the printed main grid, the nano silver powder and the second conductive material can be melted in sequence. On the one hand, it can play a sintering-aiding role for the first conductive material, promote the sintering of the first conductive material to form a dense bonding phase, thereby increasing the conductive path and reducing the volume resistance of the main grid electrode. On the other hand, the Sn-Zn-Ga-Nd alloy can act on the surface of the transparent conductive film layer of the heterojunction battery through capillary force, and after cooling, an anchoring effect will be formed, which can further improve the welding force and adhesion of the film layer. At the same time, Ga in the Sn-Zn-Ga-Nd alloy is a surface active substance, which can reduce the surface tension of the melt and improve the wetting performance of the alloy in the system. It can increase the bonding force with the welding strip during welding and improve the weldability and peeling strength of the film layer. Nd is evenly dispersed in the alloy, which can effectively enhance the oxidation resistance of Sn-Zn. At the same time, when it is welded with the welding strip, it can generate intermetallic compounds with the solder on the welding strip and disperse on the grain boundary, thereby improving the mechanical properties of the crystal, playing a role of solid solution strengthening, improving the solder resistance and peeling strength of the film layer, and avoiding the aging failure problem and poor solderability problem caused by the simple organic resin as the bonding phase. In addition, since the second conductive material can replace part of the silver conductive material, the amount of silver conductive material used is reduced, reducing the cost.
[0027] As can be seen from the above, the electrode paste provided by the present invention can improve the welding bonding strength between the electrode paste and the welding strip of the component series welding when printing the main grid during the battery manufacturing process.
[0028] In an achievable manner, the particle size of the second conductive material of the embodiment of the present invention is 1.5 μm to 3.5 μm, and the mass ratio of the Sn element, Zn element, Ga element and Nd element contained in the Sn-Zn-Ga-Nd alloy is (17.7 to 91.77): (8 to 80): (0.2 to 2): (0.03 to 0.3). In the electrode slurry provided by the embodiment of the present invention, by controlling the particle size of the second conductive material within the range of 1.5 μm to 3.5 μm, when forming the main grid on the battery, the problem that the second conductive material with a larger particle size is easy to block the grid when the main grid line is narrow and cannot be printed normally is avoided. At the same time, the embodiment of the present invention adjusts the melting point of the alloy by controlling the content of Ga element contained in the Sn-Zn-Ga-Nd alloy to meet the requirements of different curing processes. Ga is a surface active substance, which can reduce the surface tension of the melt and improve the wetting performance of the alloy in the electrode slurry. It can increase the bonding force with the welding strip during welding and improve the weldability and peel strength of the film layer. The trace rare earth element Nd is evenly dispersed in the alloy, which can effectively enhance the oxidation resistance of Sn-Zn contained in the Sn-Zn-Ga-Nd alloy. At the same time, when welded with the welding strip, the Sn-Zn contained in the Sn-Zn-Ga-Nd alloy can generate intermetallic compounds with the solder on the welding strip and disperse on the grain boundary, thereby improving the mechanical properties of the crystal, playing a role of solid solution strengthening, and then improving the solder resistance and peeling strength of the film layer.
[0029] In an optional manner, the first conductive material of the embodiment of the present invention further includes microcrystalline silver powder and spherical silver powder, and the mass ratio of nano silver powder, microcrystalline silver powder and spherical silver powder is (1-5): (5-50): (50-80). The embodiment of the present invention adds a small amount of nano silver powder. Since the melting point of nano silver powder is about 100°C, the nano silver powder can be melted first when sintering the printed main grid, which can play a sintering-aiding role for the first conductive material, promote the sintering of the first conductive material to form a dense bonding phase, thereby increasing the conductive path and reducing the volume resistance of the main grid electrode. At the same time, the spherical silver powders of the embodiment of the present invention contact each other in a point-to-point manner, and the contact area is relatively small. The microcrystalline silver powder contains a large amount of surface-to-surface contact or surface-line contact, and the contact area is relatively large. When the particle size and specific surface area of the silver conductive material are within the above range, it has a greater internal friction during relative displacement, so that the viscosity of the configured slurry is large and the curing time is reduced. At the same time, when the mass ratio of spherical silver powder to microcrystalline silver powder is within the above range, the spherical silver powder can fill the gaps between the microcrystalline silver powders, making the originally non-contacting microcrystalline silver powders contact each other, increasing the conductive path and thus improving the conductivity.
[0030] For example, the particle size of the nano silver powder in the embodiment of the present invention is 20nm to 100nm, and the specific surface area is 4m 2 / g~12m 2 / g, tap density is 2.0g / cm 3 The particle size of the microcrystalline silver powder is 0.8 μm to 2.5 μm, and the specific surface area is 0.5 m 2 / g~2m 2 / g, tap density is 4.0g / cm 3 ~6.0g / cm 3 The particle size of the spherical silver powder is 0.8 μm to 2.5 μm, and the specific surface area is 0.2 m 2 / g~1m 2 / g, tap density is 4.5g / cm 3 ~7g / cm 3 . Since the nano silver powder, microcrystalline silver powder and spherical silver powder in the embodiment of the present invention have different median particle sizes, when sintering to form the main grid, the nano silver powder with a relatively small median particle size will melt first, and the microcrystalline silver powder and spherical silver powder with a relatively large median particle size will melt later. This can reduce the pores generated during sintering, making the film layer of the electrode slurry after sintering more dense, thereby reducing the series resistance of the battery, avoiding excessive resistance in the welding area, and improving the welding tension.
[0031] In an optional manner, the electrode slurry of the embodiment of the present invention further includes an organic carrier, and the mass ratio of the first conductive material, the second conductive material and the organic carrier is (30-70): (20-40): (8-20). Under this ratio, the first conductive material and the second conductive material can be fully compatible with the organic carrier and evenly dispersed in the organic carrier, so that when the organic carrier is cured, the first conductive material and the second conductive material can be cured at the same time.
[0032] Exemplarily, the organic carrier of the embodiment of the present invention includes 1 to 10 parts of polymerizable resin, 0.1 to 3 parts of curing agent, 5 to 20 parts of organic solvent, and 0.5 to 5 parts of organic auxiliary agent. Among them, the curing agent includes hexamethylene diisocyanate. The organic solvent includes at least one of diethylene glycol butyl ether acetate, diethylene glycol butyl ether, alcohol ester dodecyl, pine alcohol, ethylene glycol phenyl ether, diethylene glycol diethyl ether and dimethyl adipate. The organic auxiliary agent may include at least one of a dispersant, an emulsifier, a defoamer and a leveling agent. The polymerizable resin may include at least one of a polyester resin, a chloroacetic acid resin, a polyurethane resin, an epoxy resin, an acrylic resin and a cellulose acetate butyrate resin.
[0033] For example: the above-mentioned polymerizable resin is preferably a vinyl chloride resin, and the vinyl chloride resin is preferably a carboxyl-modified ternary vinyl chloride resin with an average molecular weight between 1000-30000 and a hydroxyl-modified ternary vinyl chloride resin with an average molecular weight between about 2000-100000. The vinyl chloride resin molecules of the embodiment of the present invention are linear, so that the volume shrinkage rate is large during curing, and the distance between the silver powders can be reduced, thereby obtaining a lower film layer square resistance. At the same time, the carboxyl-modified resin and the hydroxyl-modified resin have more polar groups and are easy to form hydrogen bonds, so that the adhesion is greatly enhanced after cross-linking and curing with the curing agent, the chemical stability is good, the acetic acid and water vapor resistance are strong, and the aging resistance is strong, which can greatly improve the service life of the component.
[0034] Exemplarily, the organic additives of the embodiment of the present invention may include 0.2 to 2 parts of a dispersant, 0.2 to 2 parts of an emulsifier, 0.1 to 1 parts of a defoamer, and 0.1 to 1 parts of a leveling agent. Among them, the dispersant includes at least one of stearic acid, a stearic acid derivative, an unsaturated fatty acid, or an alkylamine. The emulsifier includes at least one of hydroxymethyl cellulose and sodium carboxymethyl cellulose. The leveling agent includes at least one of isophorone and diacetone alcohol. The defoamer includes at least one of a fatty acid, a fatty acid ester, and a phosphate ester.
[0035] Figure 2 The preparation flow chart of the electrode slurry provided by the embodiment of the present invention is shown as follows: Figure 2 As shown, the present invention also provides a method for preparing the electrode slurry, comprising:
[0036] Step 201: Evenly mix the organic solvent and the organic auxiliary agent, add the polymerizable resin and then add the curing agent to obtain an organic carrier.
[0037] For example: weigh the curing agent, organic solvent and organic additive according to the formula, stir at room temperature for 10min to 30min, heat to 60℃ to 80℃, add chloroacetic acid resin in batches according to proportion while stirring, keep warm for 30min to 90min, cool to room temperature, finally add the curing agent, and stir at room temperature for 30min to 60min.
[0038] Step 202: uniformly mix the first conductive material, the second conductive material and the organic carrier to obtain electrode slurry.
[0039] For example, the first conductive material, the second conductive material and the organic carrier are weighed in proportion, mixed evenly by a high-speed centrifugal mixer, stirred and dispersed at room temperature for 10 to 30 minutes, and ground by a three-roll mill to obtain an electrode slurry with a fineness of ≤6um and a viscosity of 80Pa.s to 140Pa.s (5RPM, 25°C, CP52 rotor). Among them, the second conductive material is Sn-Zn-Ga-Nd alloy, which is prepared by a two-stream atomization method, and the atomization medium is high-purity argon. High-purity argon is used to protect the entire process from alloy melting, pipeline transmission, airflow injection, cooling and powdering to avoid oxidation of the alloy powder.
[0040] The electrode paste provided by the present invention includes a first conductive material and a second conductive material. Since the first conductive material at least includes nano silver powder, the melting point of the nano silver powder is about 100°C, and the second conductive material is Sn-Zn-Ga-Nd alloy, the melting point of the second conductive material is 176°C to 198°C, when sintering the printed main grid, the nano silver powder and the second conductive material can be melted in sequence. On the one hand, it can play a sintering-aiding role for the first conductive material, promote the sintering of the first conductive material to form a dense bonding phase, thereby increasing the conductive path and reducing the volume resistance of the main grid electrode. On the other hand, the Sn-Zn-Ga-Nd alloy can act on the surface of the transparent conductive film layer of the heterojunction battery through capillary force, and after cooling, an anchoring effect will be formed, which can further improve the welding force and adhesion of the film layer. At the same time, Ga in the Sn-Zn-Ga-Nd alloy is a surface active substance, which can reduce the surface tension of the melt and improve the wetting performance of the alloy in the system. It can increase the bonding force with the welding strip during welding and improve the weldability and peeling strength of the film layer. Nd is evenly dispersed in the alloy, which can effectively enhance the oxidation resistance of Sn-Zn. At the same time, when it is welded with the welding strip, it can generate intermetallic compounds with the solder on the welding strip and disperse on the grain boundary, thereby improving the mechanical properties of the crystal, playing a role of solid solution strengthening, improving the solder resistance and peeling strength of the film layer, and avoiding the aging failure problem and poor solderability problem caused by the simple organic resin as the bonding phase. In addition, since the second conductive material can replace part of the silver conductive material, the amount of silver conductive material used is reduced, reducing the cost.
[0041] As can be seen from the above, the electrode paste provided by the present invention can improve the welding bonding strength between the electrode paste and the welding strip of the component series welding when printing the main grid during the battery manufacturing process.
[0042] In order to verify the effect of the electrode slurry provided by the embodiment of the present invention, the embodiment of the present invention is demonstrated by comparing the embodiment with the comparative example.
[0043] Embodiment 1
[0044] The electrode slurry provided by the embodiment of the present invention includes, by mass percentage: 60.5% of the first conductive material, 29.2% of Sn-Zn-Ga-Nd alloy powder (average particle size D50=1.5-3.5 μm) and 10.3% of the organic carrier.
[0045] The method for preparing the electrode slurry provided in the first embodiment of the present invention comprises the following steps:
[0046] Step 1: Preparation of the first conductive material: 1% of nano silver powder (particle size D50 = 50nm), 19% of microcrystalline silver powder (particle size D50 = 1.10um, specific surface area 1.3m 2 / g, tap density is 4.5g / cm 3 ), 80% spherical silver powder (particle size D50 = 1.20um, specific surface area 0.8m 2 / g, tap density is 5.3g / cm 3 ) to obtain a first conductive material.
[0047] The second step is the preparation of Sn-Zn-Ga-Nd alloy: by mass percentage, 0.1% Nd, 1.5% Ga, 20% Zn and 78.4% Sn are mixed to prepare Sn-Zn-Ga-Nd alloy.
[0048] Step 3, preparation of organic carrier: 24% of diethylene glycol butyl ether, 12% of dimethyl adipate and 13% of ethylene glycol phenyl ether were mixed evenly by mass percentage, and 3.0% of stearic acid and 3.0% of isophorone were added and stirred evenly, and 15% of hexamethylene diisocyanate was added while stirring to form a uniform solution, and 15% of chloroacetic acid resin and 15% of acrylic resin were added in proportion during stirring, and heated and stirred to 80°C. After being completely dissolved, stirring was continued for 60 minutes, and the mixture was allowed to stand and cool to room temperature to obtain an organic carrier.
[0049] The fourth step is to prepare electrode slurry: 60.5% of the first conductive material, 29.2% of Sn-Zn-Ga-Nd alloy powder and 10.3% of the organic carrier are mixed and stirred evenly, and dispersed and ground on a three-roll mill to obtain electrode slurry.
[0050] Step 5: Test the electrode slurry: Use a rotary viscometer (CP52 rotor viscometer) to test the viscosity at a constant temperature of 25°C. After the slurry is printed, it is dried and cured at a low temperature of 250°C, and then soldered with a φ-0.35mm tin-lead solder tape and tested for tensile strength using a KJ-1065E semi-automatic tensile tester. Then, a HALM IV tester is used to test the IV electrical performance of the battery cell.
[0051] Embodiment 2
[0052] The electrode slurry provided by the embodiment of the present invention includes, by mass percentage: 60.5% of the first conductive material, 29.2% of Sn-Zn-Ga-Nd alloy powder (average particle size D50=1.5-3.5 μm) and 10.3% of the organic carrier.
[0053] The method for preparing the electrode slurry provided in the second embodiment of the present invention comprises the following steps:
[0054] Step 1: Preparation of the first conductive material: 1% of nano silver powder (particle size D50 = 50nm), 28% of microcrystalline silver powder (particle size D50 = 1.10um, specific surface area 1.3m 2 / g, tap density is 4.5g / cm 3 ), 71% spherical silver powder (particle size D50 = 1.20um, specific surface area 0.8m 2 / g, tap density is 5.3g / cm 3 ) to obtain a first conductive material.
[0055] The second step is the preparation of Sn-Zn-Ga-Nd alloy: by mass percentage, 0.1% Nd, 1.5% Ga, 20% Zn and 78.4% Sn are mixed to prepare Sn-Zn-Ga-Nd alloy.
[0056] Step 3, preparation of organic carrier: 13% of diethylene glycol butyl ether, 26% of dimethyl adipate and 13% of ethylene glycol phenyl ether were mixed evenly by mass percentage, and 4.0% of stearic acid and 4.0% of isophorone were added and stirred evenly, and 15% of hexamethylene diisocyanate was added while stirring to form a uniform solution, and 15% of chloroacetic acid resin and 10% of acrylic resin were added in proportion during stirring, and heated and stirred to 80°C. After being completely dissolved, stirring was continued for 60 minutes, and the mixture was allowed to stand and cool to room temperature to obtain an organic carrier.
[0057] The fourth step is to prepare electrode slurry: 60.5% of the first conductive material, 29.2% of Sn-Zn-Ga-Nd alloy powder and 10.3% of the organic carrier are mixed and stirred evenly, and placed on a three-roll mill for dispersion and grinding to obtain electrode slurry.
[0058] Step 5: Test the electrode slurry: Use a rotary viscometer (CP52 rotor viscometer) to test the viscosity at a constant temperature of 25°C. After the slurry is printed, it is dried and cured at a low temperature of 250°C, and then soldered with a φ-0.35mm tin-lead solder tape and tested for tensile strength using a KJ-1065E semi-automatic tensile tester. Then, a HALM IV tester is used to test the IV electrical performance of the battery cell.
[0059] Embodiment 3
[0060] The electrode slurry provided by the embodiment of the present invention includes, by mass percentage: 60.5% of the first conductive material, 29.2% of Sn-Zn-Ga-Nd alloy powder (average particle size D50=1.5-3.5 μm) and 10.3% of the organic carrier.
[0061] The method for preparing the electrode slurry provided in the third embodiment of the present invention comprises the following steps:
[0062] Step 1: Preparation of the first conductive material: 1% of nano silver powder (particle size D50 = 50nm), 37% of microcrystalline silver powder (particle size D50 = 1.10um, specific surface area 1.3m 2 / g, tap density is 4.5g / cm 3 ), 62% spherical silver powder (particle size D50 = 1.20um, specific surface area 0.8m 2 / g, tap density is 5.3g / cm 3 ) to obtain a first conductive material.
[0063] The second step is the preparation of Sn-Zn-Ga-Nd alloy: by mass percentage, 0.1% Nd, 1.5% Ga, 20% Zn and 78.4% Sn are mixed to prepare Sn-Zn-Ga-Nd alloy.
[0064] Step 3, preparation of organic carrier: 24% of diethylene glycol butyl ether, 12% of dimethyl adipate and 13% of ethylene glycol phenyl ether were mixed evenly by mass percentage, and 3.0% of stearic acid and 3.0% of isophorone were added and stirred evenly, and 15% of hexamethylene diisocyanate was added while stirring to form a uniform solution, and 15% of chloroacetic acid resin and 15% of acrylic resin were added in proportion during stirring, and heated and stirred to 80°C. After being completely dissolved, stirring was continued for 60 minutes, and the mixture was allowed to stand and cool to room temperature to obtain an organic carrier.
[0065] The fourth step is to prepare electrode slurry: 60.5% of the first conductive material, 29.2% of Sn-Zn-Ga-Nd alloy powder and 10.3% of the organic carrier are mixed and stirred evenly, and placed on a three-roll mill for dispersion and grinding to obtain electrode slurry.
[0066] Step 5: Test the electrode slurry: Use a rotary viscometer (CP52 rotor viscometer) to test the viscosity at a constant temperature of 25°C. After the slurry is printed, it is dried and cured at a low temperature of 250°C, and then soldered with a φ-0.35mm tin-lead solder tape and tested for tensile strength using a KJ-1065E semi-automatic tensile tester. Then, a HALM IV tester is used to test the IV electrical performance of the battery cell.
[0067] Embodiment 4
[0068] The electrode slurry provided by the embodiment of the present invention includes, by mass percentage: 60.5% of the first conductive material, 29.2% of Sn-Zn-Ga-Nd alloy powder (average particle size D50=1.5-3.5 μm) and 10.3% of the organic carrier.
[0069] The method for preparing the electrode slurry provided in the fourth embodiment of the present invention comprises the following steps:
[0070] Step 1: Preparation of the first conductive material: 3% of nano silver powder (particle size D50 = 50nm), 28% of microcrystalline silver powder (particle size D50 = 1.10um, specific surface area 1.3m 2 / g, tap density is 4.5g / cm 3 ), 69% spherical silver powder (particle size D50 = 1.20um, specific surface area 0.8m 2 / g, tap density is 5.3g / cm 3 ) to obtain a first conductive material.
[0071] The second step is the preparation of Sn-Zn-Ga-Nd alloy: by mass percentage, 0.1% Nd, 1.5% Ga, 20% Zn and 78.4% Sn are mixed to prepare Sn-Zn-Ga-Nd alloy.
[0072] Step 3, preparation of organic carrier: 24% of diethylene glycol butyl ether, 12% of dimethyl adipate and 13% of ethylene glycol phenyl ether were mixed evenly by mass percentage, and 3.0% of stearic acid and 3.0% of isophorone were added and stirred evenly, and 15% of hexamethylene diisocyanate was added while stirring to form a uniform solution, and 15% of chloroacetic acid resin and 15% of acrylic resin were added in proportion during stirring, and heated and stirred to 80°C. After being completely dissolved, stirring was continued for 60 minutes, and the mixture was allowed to stand and cool to room temperature to obtain an organic carrier.
[0073] The fourth step is to prepare electrode slurry: 60.5% of the first conductive material, 29.2% of Sn-Zn-Ga-Nd alloy powder and 10.3% of the organic carrier are mixed and stirred evenly, and placed on a three-roll mill for dispersion and grinding to obtain electrode slurry.
[0074] Step 5: Test the electrode slurry: Use a rotary viscometer (CP52 rotor viscometer) to test the viscosity at a constant temperature of 25°C. After the slurry is printed, it is dried and cured at a low temperature of 250°C, and then soldered with a φ-0.35mm tin-lead solder tape and tested for tensile strength using a KJ-1065E semi-automatic tensile tester. Then, a HALM IV tester is used to test the IV electrical performance of the battery cell.
[0075] Embodiment 5
[0076] The electrode slurry provided by the embodiment of the present invention includes, by mass percentage, 50% of a first conductive material, 30% of Sn-Zn-Ga-Nd alloy powder (average particle size D50=1.5-3.5 μm) and 20% of an organic carrier.
[0077] The method for preparing the electrode slurry provided in the fifth embodiment of the present invention comprises the following steps:
[0078] Step 1: Preparation of the first conductive material: 1% of nano silver powder (particle size D50 = 50nm), 28% of microcrystalline silver powder (particle size D50 = 1.10um, specific surface area 1.3m 2 / g, tap density is 4.5g / cm 3 ), 71% spherical silver powder (particle size D50 = 1.20um, specific surface area 0.8m 2 / g, tap density is 5.3g / cm 3 ) to obtain a first conductive material.
[0079] The second step is the preparation of Sn-Zn-Ga-Nd alloy: by mass percentage, 0.1% Nd, 1.5% Ga, 20% Zn and 78.4% Sn are mixed to prepare Sn-Zn-Ga-Nd alloy.
[0080] Step 3, preparation of organic carrier: 13% of diethylene glycol butyl ether, 26% of dimethyl adipate and 13% of ethylene glycol phenyl ether were mixed evenly by mass percentage, and 4.0% of stearic acid and 4.0% of isophorone were added and stirred evenly, and 15% of hexamethylene diisocyanate was added while stirring to form a uniform solution, and 15% of chloroacetic acid resin and 10% of acrylic resin were added in proportion during stirring, and heated and stirred to 80°C. After being completely dissolved, stirring was continued for 60 minutes, and the mixture was allowed to stand and cool to room temperature to obtain an organic carrier.
[0081] The fourth step is to prepare electrode slurry: 50% of the first conductive material, 30% of Sn-Zn-Ga-Nd alloy powder and 20% of the organic carrier are mixed and stirred evenly, and then placed on a three-roll mill for dispersion and grinding to obtain electrode slurry.
[0082] Step 5: Test the electrode slurry: Use a rotary viscometer (CP52 rotor viscometer) to test the viscosity at a constant temperature of 25°C. After the slurry is printed, it is dried and cured at a low temperature of 250°C, and then soldered with a φ-0.35mm tin-lead solder tape and tested for tensile strength using a KJ-1065E semi-automatic tensile tester. Then, a HALM IV tester is used to test the IV electrical performance of the battery cell.
[0083] Embodiment 6
[0084] The electrode slurry provided by the embodiment of the present invention includes, by mass percentage, 50% of a first conductive material, 40% of Sn-Zn-Ga-Nd alloy powder (average particle size D50=1.5-3.5 μm) and 10% of an organic carrier.
[0085] The method for preparing the electrode slurry provided in the sixth embodiment of the present invention comprises the following steps:
[0086] Step 1: Preparation of the first conductive material: 1% of nano silver powder (particle size D50 = 50nm), 28% of microcrystalline silver powder (particle size D50 = 1.10um, specific surface area 1.3m 2 / g, tap density is 4.5g / cm 3 ), 71% spherical silver powder (particle size D50 = 1.20um, specific surface area 0.8m 2 / g, tap density is 5.3g / cm 3 ) to obtain a first conductive material.
[0087] The second step is the preparation of Sn-Zn-Ga-Nd alloy: by mass percentage, 0.1% Nd, 1.5% Ga, 20% Zn and 78.4% Sn are mixed to prepare Sn-Zn-Ga-Nd alloy.
[0088] Step 3, preparation of organic carrier: 13% of diethylene glycol butyl ether, 26% of dimethyl adipate and 13% of ethylene glycol phenyl ether were mixed evenly by mass percentage, and 4.0% of unsaturated fatty acid and 4.0% of diacetone alcohol were added and stirred evenly, and 15% of hexamethylene diisocyanate was added while stirring to form a uniform solution, and 15% of chloroacetic acid resin and 10% of acrylic resin were added in proportion during stirring, and heated and stirred to 80°C. After being completely dissolved, stirring was continued for 60 minutes, and the solution was cooled to room temperature to obtain an organic carrier.
[0089] The fourth step is to prepare electrode slurry: 50% of the first conductive material, 40% of Sn-Zn-Ga-Nd alloy powder and 10% of the organic carrier are mixed and stirred evenly, and then placed on a three-roll mill for dispersion and grinding to obtain electrode slurry.
[0090] Step 5: Test the electrode slurry: Use a rotary viscometer (CP52 rotor viscometer) to test the viscosity at a constant temperature of 25°C. After the slurry is printed, it is dried and cured at a low temperature of 250°C, and then soldered with a φ-0.35mm tin-lead solder tape and tested for tensile strength using a KJ-1065E semi-automatic tensile tester. Then, a HALM IV tester is used to test the IV electrical performance of the battery cell.
[0091] Embodiment 7
[0092] The electrode slurry provided by the embodiment of the present invention includes, by mass percentage: 60.5% of the first conductive material, 29.2% of Sn-Zn-Ga-Nd alloy powder (average particle size D50=1.5-3.5 μm) and 10.3% of the organic carrier.
[0093] The method for preparing the electrode slurry provided in the seventh embodiment of the present invention comprises the following steps:
[0094] Step 1: Preparation of the first conductive material: 1% of nano silver powder (particle size D50 = 50nm), 19% of microcrystalline silver powder (particle size D50 = 1.10um, specific surface area 1.3m 2 / g, tap density is 4.5g / cm 3 ), 80% spherical silver powder (particle size D50 = 1.20um, specific surface area 0.8m 2 / g, tap density is 5.3g / cm 3 ) to obtain a first conductive material.
[0095] The second step is the preparation of Sn-Zn-Ga-Nd alloy: by mass percentage, 0.2% Nd, 2% Ga, 20% Zn and 77.8% Sn are mixed to prepare Sn-Zn-Ga-Nd alloy.
[0096] Step 3, preparation of organic carrier: 24% of diethylene glycol butyl ether, 12% of dimethyl adipate and 13% of ethylene glycol phenyl ether were mixed evenly by mass percentage, and 3.0% of stearic acid and 3.0% of isophorone were added and stirred evenly, and 15% of hexamethylene diisocyanate was added while stirring to form a uniform solution, and 15% of chloroacetic acid resin and 15% of acrylic resin were added in proportion during stirring, and heated and stirred to 80°C. After being completely dissolved, stirring was continued for 60 minutes, and the mixture was allowed to stand and cool to room temperature to obtain an organic carrier.
[0097] The fourth step is to prepare electrode slurry: 60.5% of the first conductive material, 29.2% of Sn-Zn-Ga-Nd alloy powder and 10.3% of the organic carrier are mixed and stirred evenly, and dispersed and ground on a three-roll mill to obtain electrode slurry.
[0098] Step 5: Test the electrode slurry: Use a rotary viscometer (CP52 rotor viscometer) to test the viscosity at a constant temperature of 25°C. After the slurry is printed, it is dried and cured at a low temperature of 250°C, and then soldered with a φ-0.35mm tin-lead solder tape and tested for tensile strength using a KJ-1065E semi-automatic tensile tester. Then, a HALM IV tester is used to test the IV electrical performance of the battery cell.
[0099] Embodiment 8
[0100] The electrode slurry provided by the embodiment of the present invention includes, by mass percentage: 60.5% of the first conductive material, 29.2% of Sn-Zn-Ga-Nd alloy powder (average particle size D50=1.5-3.5 μm) and 10.3% of the organic carrier.
[0101] The method for preparing the electrode slurry provided in the eighth embodiment of the present invention comprises the following steps:
[0102] Step 1: Preparation of the first conductive material: 1% of nano silver powder (particle size D50 = 50nm), 19% of microcrystalline silver powder (particle size D50 = 1.10um, specific surface area 1.3m 2 / g, tap density is 4.5g / cm 3 ), 80% spherical silver powder (particle size D50 = 1.20um, specific surface area 0.8m 2 / g, tap density is 5.3g / cm 3 ) to obtain a first conductive material.
[0103] The second step is the preparation of Sn-Zn-Ga-Nd alloy: by mass percentage, 0.5% Nd, 5% Ga, 20% Zn and 74.5% Sn are mixed to prepare Sn-Zn-Ga-Nd alloy.
[0104] Step 3, preparation of organic carrier: 24% of diethylene glycol butyl ether, 12% of dimethyl adipate and 13% of ethylene glycol phenyl ether were mixed evenly by mass percentage, and 3.0% of stearic acid and 3.0% of isophorone were added and stirred evenly, and 15% of hexamethylene diisocyanate was added while stirring to form a uniform solution, and 15% of chloroacetic acid resin and 15% of acrylic resin were added in proportion during stirring, and heated and stirred to 80°C. After being completely dissolved, stirring was continued for 60 minutes, and the mixture was allowed to stand and cool to room temperature to obtain an organic carrier.
[0105] The fourth step is to prepare electrode slurry: 60.5% of the first conductive material, 29.2% of Sn-Zn-Ga-Nd alloy powder and 10.3% of the organic carrier are mixed and stirred evenly, and dispersed and ground on a three-roll mill to obtain electrode slurry.
[0106] Step 5: Test the electrode slurry: Use a rotary viscometer (CP52 rotor viscometer) to test the viscosity at a constant temperature of 25°C. After the slurry is printed, it is dried and cured at a low temperature of 250°C, and then soldered with a φ-0.35mm tin-lead solder tape and tested for tensile strength using a KJ-1065E semi-automatic tensile tester. Then, a HALM IV tester is used to test the IV electrical performance of the battery cell.
[0107] Comparative Example 1
[0108] Comparative Example 1 of the present invention uses externally purchased main grid silver paste, which does not contain the Sn-Zn-Ga-Nd alloy and nano silver powder of the embodiment of the invention.
[0109] The test results of the electrode slurries provided in this embodiment and the comparative example are as follows:
[0110]
[0111] As can be seen from the above table, the welding tension in Examples 1 to 8 is much higher than that in Comparative Example 1, and the efficiency is better than that of the battery in Comparative Example 1. Therefore, by using nano silver powder and Sn-Zn-Ga-Nd alloy in the electrode slurry of the embodiment of the present invention, the melting point of Sn-Zn-Ga-Nd alloy is 176°C to 198°C. When sintering the printed main grid, the nano silver powder and Sn-Zn-Ga-Nd alloy can be melted in sequence, which can help the first conductive material to be sintered, and promote the sintering of the first conductive material to form a dense bonding phase, thereby increasing the conductive path, reducing the volume resistance of the main grid electrode, and improving the welding tension. At the same time, by reducing the use of the first conductive material, the welding tension and battery conversion efficiency of Examples 5 and 6 are still greater than those of Comparative Example 1. That is to say, the second conductive material can replace part of the silver conductive material, thereby reducing the use of the first conductive material and reducing the cost.
[0112] The above is only a specific embodiment of the present invention. Obviously, various modifications and combinations can be made without departing from the spirit and scope of the present invention. Accordingly, this specification and the drawings are only exemplary illustrations of the present invention as defined by the attached claims, and are deemed to have covered any and all modifications, changes, combinations or equivalents within the scope of the present invention. Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is intended to include these changes and variations. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope of protection of the claims.
Claims
1. An electrode slurry, characterized in that: include: A first conductive material and a second conductive material, the first conductive material at least includes nano silver powder, the second conductive material is a Sn-Zn-Ga-Nd alloy, the melting point of the second conductive material is 176°C to 198°C, the particle size of the second conductive material is 1.5μm to 3.5μm, and the mass ratio of Sn element, Zn element, Ga element and Nd element contained in the Sn-Zn-Ga-Nd alloy is (17.7 to 91.77): (8 to 80): (0.2 to 2): (0.03 to 0.3).
2. The electrode slurry according to claim 1, characterized in that: The first conductive material also includes microcrystalline silver powder and spherical silver powder, and the mass ratio of the nano silver powder, microcrystalline silver powder and spherical silver powder is (1-5): (5-50): (50-80).
3. The electrode slurry according to claim 2, characterized in that: The particle size of the nano silver powder is 20nm to 100nm, and the specific surface area is 4m 2 / g~12m 2 / g, tap density is 2.0g / cm 3 The particle size of the microcrystalline silver powder is 0.8 μm to 2.5 μm, and the specific surface area is 0.5 m 2 / g~2m 2 / g, tap density is 4.0g / cm 3 ~6.0g / cm 3 The particle size of the spherical silver powder is 0.8 μm to 2.5 μm, and the specific surface area is 0.2 m 2 / g~1m 2 / g, tap density is 4.5g / cm 3 ~7g / cm 3 .
4. The electrode slurry according to any one of claims 1 to 3, characterized in that: The electrode slurry further includes an organic carrier, and the mass ratio of the first conductive material, the second conductive material and the organic carrier is (30-70): (20-40): (8-20).
5. The electrode slurry according to claim 4, characterized in that: In parts by mass, the organic carrier includes 1 to 10 parts of a polymerizable resin, 0.1 to 3 parts of a curing agent, 5 to 20 parts of an organic solvent, and 0.5 to 5 parts of an organic auxiliary agent.
6. The electrode slurry according to claim 5, characterized in that: The polymerizable resin includes at least one of polyester resin, chloroacetic acid resin, polyurethane resin, epoxy resin, acrylic resin and cellulose acetate butyrate resin.
7. The electrode slurry according to claim 5, characterized in that: The molecular structure of the chlorovinyl resin is linear, and the chlorovinyl resin includes carboxyl modified resin and hydroxyl modified resin.
8. A method for preparing an electrode slurry according to any one of claims 1 to 7, characterized in that: include: The organic solvent and the organic auxiliary agent are mixed evenly, the polymerizable resin is added, and then the curing agent is added to obtain an organic carrier; The first conductive material, the second conductive material and the organic carrier are mixed uniformly to obtain an electrode slurry.
9. A photovoltaic cell, characterized in that: The photovoltaic cell has grid lines on its surface, and the material of the grid lines is the electrode slurry according to any one of claims 1 to 7.
Citation Information
Patent Citations
Conductive paste
CN110853794A
Universal back electrode silver paste for PERC single-sided and double-sided batteriesand preparation method thereof
CN111403077A